Next generation sequencing of 134 children with autism spectrum disorder and regression - Yin, Jiani; Chun, Chun-An; Zavadenko, Nikolay N.; Pechatnikova, Natalia L.; Naumova, Oxana Yu; Doddapaneni, Harsha V.; Hu, Jianhong; Muzny, Donna M.; Schaaf, Christian P.; Grigorenko, Elena L. (Genes, 2020)
Approximately 30% of individuals with autism spectrum disorder (ASD) experience developmental regression, the etiology of which remains largely unknown. We performed a complete literature search and identified 47 genes that had been implicated in such cases. We sequenced these genes in a preselected cohort of 134 individuals with regressive autism. In total, 16 variants in 12 genes with evidence supportive of pathogenicity were identified. They were classified as variants of uncertain significance based on ACMG standards and guidelines. Among these were recurring variants in GRIN2A and PLXNB2, variants in genes that were linked to syndromic forms of ASD (GRIN2A, MECP2, CDKL5, SCN1A,PCDH19, UBE3A, and SLC9A6), and variants in the form of oligogenic heterozygosity (EHMT1, SLC9A6, and MFSD8).